Transport layer performance combining multipath and network coding in mobile satellite networks. (11th October 2017) - Giambene, Giovanni; Luong, Doanh Kim; Le, Van Anh; de Cola, Tomaso; Muhammad, Muhammad
Summary: Satellite networks are expected to support multimedia traffic flows, offering high capacity with quality of service guarantees. In this paper, we consider future satellite networks able to exploit multiple paths to reach mobile users also by means of a terrestrial complementary coverage. The interest is to exploit the path diversity by adopting network coding at a shim layer between Internet protocol and media access control. We have proposed several variants of network‐coding schemes with different organizations in terms of interflow and intraflow encoding, where the packets generated by the encoder are split and sent on different paths. Our path‐based network coding (PBNC) techniques have been combined with multipath transmission control protocol (MPTCP) and TCP at transport layer, thus obtaining PBNC‐MPTCP and PBNC‐TCP. We have evaluated the performance of these techniques by means of Ns‐2 simulations. A cross‐layer criterion has been adopted to determine the settings of the encoders. Our PBNC‐based schemes have shown better goodput performance than a benchmark scheme considering 2 different scenarios (one with symmetrical paths and one with unbalanced paths) in the presence of GOOD/BAD mobile channels. Abstract : In this paper, we consider future satellite networks able to exploit multiple paths to reach mobile users, characterized by GOOD/BAD channels. The interest is to exploit the path diversity by adopting network coding at a shim layer between IP and MAC. A cross‐layer approach has been adopted in order to determine the settings of the encoders that improve the performance at transport layer.